Exposure of Chronic Obstructive Pulmonary Disease Patients to Particulate Matter: Relationships between Personal and Ambient Air Concentrations - Ebelt, Stefanie T.; Petkau, A. John; Vedal, Sverre; Fisher, Teri V.; Brauer, Michael (Journal of the Air & Waste Management Association (1995), 2000)
Most time-series studies of particulate air pollution and acute health outcomes assess exposure of the study population using fixed-site outdoor measurements. To address the issue of exposure misclassification, we evaluate the relationship between ambient particle concentrations and personal exposures of a population expected to be at risk of particle health effects. Sampling was conducted within the Vancouver metropolitan area during April-September 1998. Sixteen subjects (non-smoking, ages 54-86) with physician-diagnosed chronic obstructive pulmonary disease (COPD) wore personal PM 2 5 monitors for seven 24-hr periods, randomly spaced approximately 1.5 weeks apart. Time-activity logs and dwelling characteristics data were also obtained for each subject. Daily 24-hr ambient PM 10 and PM 2.5 concentrations were measured at five fixed sites spaced throughout the study region. SO 4 2- , which is found almost exclusively in the fine particle fraction and which does not have major indoor sources, was measured in all PM 2 5 samples as an indicator of accumulation mode particu-late matter of ambient origin.